2022
DOI: 10.1038/s41377-022-00924-3
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven design of high-performance MASnxPb1-xI3 perovskite materials by machine learning and experimental realization

Abstract: The photovoltaic performance of perovskite solar cell is determined by multiple interrelated factors, such as perovskite compositions, electronic properties of each transport layer and fabrication parameters, which makes it rather challenging for optimization of device performances and discovery of underlying mechanisms. Here, we propose and realize a novel machine learning approach based on forward-reverse framework to establish the relationship between key parameters and photovoltaic performance in high-prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 51 publications
0
24
0
1
Order By: Relevance
“…Another case study presented by Xia et al [ 59 ] combined ML techniques with an efficient forward‐inverse method to research M A S n x P b 1 x I 3 material and explored high‐ performance PSCs. With 14 physicochemical parameters and the Sn–Pb ratio as inputs, the E g model of M A S n x P b 1 x I 3 was first developed for forward analysis, and the asymmetrically bowing relationship between the Sn–Pb ratio and the E g of OMHP was used.…”
Section: Results and Analysismentioning
confidence: 99%
“…Another case study presented by Xia et al [ 59 ] combined ML techniques with an efficient forward‐inverse method to research M A S n x P b 1 x I 3 material and explored high‐ performance PSCs. With 14 physicochemical parameters and the Sn–Pb ratio as inputs, the E g model of M A S n x P b 1 x I 3 was first developed for forward analysis, and the asymmetrically bowing relationship between the Sn–Pb ratio and the E g of OMHP was used.…”
Section: Results and Analysismentioning
confidence: 99%
“…They also gave a corresponding explanation based on XPS and FTIR results that the capping layer on top stabilizes 3 by changing the surface structure and chemistry, which match the previous experiment regulations 167,168 . Besides, by machine learning and experiment verification, Cai et al confirmed the ratio of Sn: Pb in MASn x Pb 1 -xI 3 holding an Sn-Pb alloy within the perovskite crystal 169 .…”
Section: Energy Advances Accepted Manuscriptmentioning
confidence: 99%
“…166,167 Besides, by machine learning and experimental verification, Cai et al confirmed the ratio of Sn: Pb in MASn x Pb 1 - x I 3 holding an Sn–Pb alloy within the perovskite crystal. 168…”
Section: Perovskitementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the material screening for the photovoltaic applications, 1,100 the suitability of artificial intelligence in predicting the stability, and the reap, rest, and recovery (3R) of halide perovskites has been also reported and may applied also to PIM-based IPVs to boost their credibility for future practical applications. 101…”
Section: Prospect Ipv Absorbersmentioning
confidence: 99%